Making the most out of the EPA Research Summer School: from a group exercise to an international collaborative study protocol - C. Tapoi; R. De Filippis; C. Noël; D. Almeida; D. Gurrea Salas; K. Mieze; A. Pushko; M. Pinto Da Costa (European Psychiatry, 2022)
Introduction The 2021 Research Summer School took place virtually, and 7 psychiatric trainees or early career psychiatrists (ECPs) from 7 different European countries participated in a working group on how to conduct a cross-sectional survey study.